Use of religious language in advertising (Journal of Parents and Teachers, 2025)
Based on the undeniable reality that society is growing in terms of mass consumption, which leads to an existential void in human beings, this article shows us how this way of life affects religion, which is so closely linked to human existence. Thus, we are presented with some advertisements taken from magazines in which it could be said that religious language is being manipulated for advertising purposes. However, beyond possible manipulation, the question is what lifestyle is being proposed by advertising, what values shape life, and whether they lead us to be ‘faithful devotees of having rather than being.
Keywords: advertising, religious language, consumerism, existential emptiness, manipulation